ШЫҒЫС ОЙШЫЛЛАРЫ ЕРКИН ПИКИРДИ РАЎАЖЛАНДЫРЫЎШЫ ФАКТОРЛАР ҲӘМ ШӘРТ-ШӘРАЯТЛАР ҲАҚҚЫНДА - Кенжебаева, К.Б. (ILIM hám JÁMIYET, 2016)
The article deals with the didactic works of Eastern thinkers. The author studies the full, deep and qualitative mastery by students of knowledge, habits and skills, ways of training for their free use special attention is paid to the role of a teacher in this work.